1996
DOI: 10.1159/000154319
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Thaiassermia Genes in Israel: Deletional and Nondeletional Mutations in Patients of Various Origins

Abstract: The α-thalassemia mutations in 34 Jewish patients of various origins and in 13 Arab patients have been identified using DNA technologies. Middle Eastern Jews and Arabs have both deletional and nondeletional mutations, but in the former the most frequent mutation is the Mediterranean deletion while in Arabs it is the polyadenylation signal mutation. Another nondeletional mutation, the 5 bp deletion at the IVS1 splice donor site has only been found in Arabs. Yemenite and European Jews have only deletional mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
1
1
Order By: Relevance
“…The majority of Ashkenazi Jewish patients (88.5%) carried the ‐α 3.7 deletion, which was the only deletion found in this ethnic group, in agreement with previous publications . A few point mutations were identified, comprising 11.5% of the genetic changes in this group.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of Ashkenazi Jewish patients (88.5%) carried the ‐α 3.7 deletion, which was the only deletion found in this ethnic group, in agreement with previous publications . A few point mutations were identified, comprising 11.5% of the genetic changes in this group.…”
Section: Resultssupporting
confidence: 91%
“…The dispersion of the mutations among different populations in our cohort is in agreement with previous publications . As previously published, in contrast to other ethnicities in Israel, most of the Muslim Arab patients carried point mutations (51.6%, Table ) . In addition, among patients with HbH disease, the percentage of Muslim Arab patients was high (69%).…”
Section: Discussionsupporting
confidence: 92%
“…This mutation abolishes an MseI recognition site. The −␣ 20.5 deletion previously found in one Israeli Arab family [10] was not encountered in the present study.…”
Section: Analysis Of Mutations and Rearrangementscontrasting
confidence: 63%
“…Previous studies on ␣-thalassemia in Israel revealed that it is prevalent in Jews of Yemenite, Iraqi, and Kurdish origin, based on the presence of Hb Bart's (␥ 4 ) in cord blood of newborns [7][8][9]. Evaluation at the molecular level has been sparse, with the largest series including only 47 individuals [10]. Other reports were sporadic and demonstrated diverse findings including novel point mutations [11,12], a novel deletion [13], and four ␣-globin chain variants: Hb Hasharon (␣ 47 Asp-His) [14], Hb Shaare-Zedek (␣ 56 Lys-Glu) [15], Hb Petah Tikva (␣ 110 Ala-Asp) [16], and Hb Taybe (denoted throughout this work as ␣1 ⌬T39) [17].…”
Section: Introductionmentioning
confidence: 99%